2016
DOI: 10.7554/elife.19706
|View full text |Cite
|
Sign up to set email alerts
|

Structural snapshots of Xer recombination reveal activation by synaptic complex remodeling and DNA bending

Abstract: Bacterial Xer site-specific recombinases play an essential genome maintenance role by unlinking chromosome multimers, but their mechanism of action has remained structurally uncharacterized. Here, we present two high-resolution structures of Helicobacter pylori XerH with its recombination site DNA difH, representing pre-cleavage and post-cleavage synaptic intermediates in the recombination pathway. The structures reveal that activation of DNA strand cleavage and rejoining involves large conformational changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 71 publications
(131 reference statements)
2
29
1
Order By: Relevance
“…The C-terminal helix αM is swapped between the two subunits, interacting with a cleft on the surface of the partner ( Figure 2 A); αL that carries the nucleophile tyrosine interacts with its own subunit in cis . Similar arrangement was observed in the structures of Cre, XerH, and λ integrase ( Bebel et al., 2016 , Biswas et al., 2005 , Guo et al., 1997 ) ( Figures S1 E and S1F) and was proposed to play a role in intersubunit communication. However, those structures showed a cyclic exchange in homo-tetrameric assemblies ( Figure S1 F), whereas in the Int 82N -CI5 complex, the swap is reciprocal between the two protein subunits and constitutes a major interface holding the dimer together.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The C-terminal helix αM is swapped between the two subunits, interacting with a cleft on the surface of the partner ( Figure 2 A); αL that carries the nucleophile tyrosine interacts with its own subunit in cis . Similar arrangement was observed in the structures of Cre, XerH, and λ integrase ( Bebel et al., 2016 , Biswas et al., 2005 , Guo et al., 1997 ) ( Figures S1 E and S1F) and was proposed to play a role in intersubunit communication. However, those structures showed a cyclic exchange in homo-tetrameric assemblies ( Figure S1 F), whereas in the Int 82N -CI5 complex, the swap is reciprocal between the two protein subunits and constitutes a major interface holding the dimer together.…”
Section: Resultssupporting
confidence: 75%
“…We envision that two DNA-bound dimers first come together to assemble a tetramer with straight DNA, which then undergoes activation by DNA bending to create an arrangement similar to active structures of other tyrosine recombinases ( Biswas et al., 2005 , Guo et al., 1997 ). This mechanism is supported by the fact that our oligomerization antagonist peptide blocks DNA cleavage and by studies of the XerH- dif H complex, which showed that synaptic tetramers first assemble in a pre-catalytic state with straight DNA and are then activated via structural rearrangement and DNA bending ( Bebel et al., 2016 ). As shown on Movie S1 , the conformational changes required for tetramerization are straightforward to visualize based on the λInt-COC′ synaptic complex structure by modeling.…”
Section: Discussionmentioning
confidence: 63%
“…Like Tre, XerH tyrosine recombinase from Helicobacter pylori also acts on an asymmetrical DNA substrate; one arm contains an added base pair near the middle relative to the other. In contrast to Tre, where the same amino acids must engage different bases on each side of the complex, the crystal structure of XerH in complex with its DNA substrate shows largely similar contacts with both arms ( 52 ). As in Tre/ loxLTR , flexibility in both the DNA and the protein are important for recognizing of the asymmetrical substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of the dif sequence in vesicle DNA suggests that OMVs are mainly formed by those cells that require chromosome dimer resolution, the frequency of which has been estimated to range between 10 to 40% per cell cycle [51] [39]. Chromosome dimer resolution requires exact spatial and temporal timing of XerC/XerD activity to the division septum just before separation of daughter cells, which is accomplished by binding of the XerC/XerD enzymes to the divisome protein FtsK [51] [52]. The excision of small DNA fragements during this process has not been reported; only single strand lesions and re-annealing are required for chromosome dimer resolution [52].…”
Section: The Chromosomal Region Around the Terminus Of Replication Ismentioning
confidence: 99%
“…Chromosome dimer resolution requires exact spatial and temporal timing of XerC/XerD activity to the division septum just before separation of daughter cells, which is accomplished by binding of the XerC/XerD enzymes to the divisome protein FtsK [51] [52]. The excision of small DNA fragements during this process has not been reported; only single strand lesions and re-annealing are required for chromosome dimer resolution [52]. However, the XerC/XerD enzymes are dif sequence specific tyrosine recombinases that have been used to construct markerless gene deletions [53] [54].…”
Section: The Chromosomal Region Around the Terminus Of Replication Ismentioning
confidence: 99%